Two-fluid Mixing Enhancement by Using a Static Turbulence Generator - Ortega, P.; McGrath, G.; Rojas-Solorzano, L. (SPE, 2001)
The numerical simulation of a static T-type mixer for turbulent mixing of miscible liquids is reported. The simulation was carried out using CFX, a commercial computational fluid dynamic simulator. The effect of mixing intensification caused by turbulence generators placed downstream of the injection point of the Tee was evaluated in terms of reduction in mixing length for a given mixture quality, uniformity of turbulence intensity and efficiency of energy conversion to useful mixing energy. The mixing quality for an intensified and conventional T-type mixer was compared, and the turbulence generator geometry was optimized. Main stream Reynolds numbers between 50000 and 100000 were considered for additive volume ratios in the range 0.1 - 10%. Selected simulations were validated with experimental data available in the literature for conventional smooth T-type mixers (no ribs). Results were in good agreement with experimental correlations available at high Reynolds numbers. Simulations demonstrated that mixing enhancement was efficient with turbulence generators, extending the Reynolds number range for which compact, low pressure-drop devices may be used for intense mixing. The optimum geometry for turbulence generators was evaluated using criteria based on energetic and spatial efficiency and in all cases the simple Tee was used as the point of reference. Finally, practical design correlations are presented to enable the mixing quality of two miscible streams to be estimated for a simple Tee with and without additional turbulence generators over a range of Reynolds numbers and injection conditions.
Keywords: Research Subject Categories::TECHNOLOGY::Engineering mechanics; mechanical engineering